Optical transmission property of electro-optic dye-doped polymer waveguide - Shaktur, Khaled; Ab Rahman, Mohammad; Mohammad, Rahmah (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Optical transmission of electro-optic effect polymers from dye-doped acrylate copolymer and guest–host polysulfones was evaluated with varying electric fields at room temperature. The dye-doped copolymer behaved differently from the guest–host polymer system upon the application of the electric field. Time-dependent phenomena were obtained due to relaxation. The dye hyperpolarizability affected the manner in which the dye is poled.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 799-806
Keywords: optyka; doped-acrylate copolymer with DR-1; optical transmission; electro-optic effect